Application of the Technology Acceptance Model (TAM) in testing the acceptance model of application BORN (Business & Operational Risk Management Nindya Karya) - Bunga Natalia Hutauruk; Saparso Saparso (Institute of Computer Science (IOCS), 2023)
This research aims to determine the effect of Perceived Ease Of Use Perceived Ease Of Use and Perceived Usefulness on Behavioral Intention with Attitude Towards Using as an Intervening Variable in the BORN (Business & Operation Risk Management Nindya Karya) application. The population in this study were all employees of PT. Nindya Karya who used BORN (Business & Operation Risk Management Nindya), especially in the scope of the project in accordance with the PIC Risk determination of the project risk officer and processed using Structural Equation Model (SEM) analysis with SEM PLS software. Based on the research results obtained empirical facts in the form of: 1) There is a significant positive effect the variable Perceived Usefulness influences Behavioral Intention; 2) There is a positive influence of the Perceived Ease of Use variable on Behavioral Intention; 3) There is a significant positive effect of Perceived Usefulness variable on Attitude Towards Using; 4) There is a significant positive effect of the Perceived Ease of Use variable on Attitude Towards Using; 5) There is a positive influence of Attitude Towards Using variable on Behavioral Intention; 6) Perceived Usefulness does not significantly mediate the positive effect on Behavioral Intention mediated by Attitude Towards Using; 7) Perceived Ease of Use does not significantly mediate the positive effect of Behavioral Intention on Attitude Towards Using.